MANIFEST AND LATENT FUNCTIONS IN THE MERARIQ TRADITION OF THE SASAK TRIBE, LOMBOK, WEST NUSA TENGGARA - A Zahid (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2023)
Merariq is one of the traditions of the Sasak people of Lombok, West Nusa Tenggara which is still maintainMerariq is one of the traditions of the Sasak people of Lombok, West Nusa Tenggara which is still maintained to this day. The uniqueness of this tradition has a function that can be described in manifest and latent forms. So, the aim of mapping this function is so that there is no ambiguity in the merariq process because merariq could be the legality of the bride and groom's relationship if it is not approved by one of the family members. This research uses a qualitative method with a library approach, with data sources from books and articles that have been prepared and adapted to the object of the research study. The results of this research show that not everything in the merariq process is an actual or manifest function, but there are also latent functions contained, for example in the form of Education, Social Stratification, and Conflicted to this day. The uniqueness of this tradition has a function that can be described in manifest and latent forms. So, the aim of mapping this function is so that there is no ambiguity in the merariq process because merariq could be the legality of the bride and groom's relationship if it is not approved by one of the family members. This research uses a qualitative method with a library approach, with data sources from books and articles that have been prepared and adapted to the object of the research study. The results of this research show that not everything in the merariq process is an actual or manifest function, but there are also latent functions contained, for example in the form of Education, Social Stratification, and Conflict.